Influence of PVP on the morphologies of Bi2S3 nanostructures synthesized by solvothermal method - Anukorn Phuruangrat (2018)
Different morphologies of Bi 2 S 3 nanostructures were synthesized by a 180°C and 12 h solvothermal reaction of solutions containing Bi(NOmiddot;5H and thioacetamide (CHSNH in diethylene glycol (DEG) as a solvent. The as-synthesized Bi 2 S 3 products characterized by XRD, Raman spectroscopy, SEM, and TEM showed that they were well-crystallized orthorhombic Bi 2 S 3 phase with morphologies of nanorod-like, sheaf-like, carnation-like, and microspherical, controlled by different contents of polyvinylpyrrolidone (PVP) in the solutions. Based on the experimental results, a growth mechanism was also proposed and discussed. © 2013 Anukorn Phuruangrat et al.